ผลทางกฎหมายของสัญญาชาร์เตอร์เรือแบบมีกำหนดเวลาตามแบบมาตรฐานของนิวยอร์ค โปรดิวซ์ เอ็กซเนจ์ ค.ศ. 1993 - ชวนรรถ อยู่สุวรรณ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
This Thesis has the purpose to study characteristics of the New York Produce Exchange Time Charter Form 1993 (NYPE 93) and the foreign laws concerning its enforcement and compare with Thai laws particularly the cases where it may not be enforceable in accordance with the intention of the parties. The research finds out that there is no Thai law on Time Charter and the general laws on Obligation and Contract may apply to the dispute. However, since the contract aims at transportation of goods by sea and is based on Common Law, there are problems regarding its legal effect as follows: 1) Criteria for determination of the charterer s right in cancelling the contract at the time of vessel s delivery as per Cancelling Clause and after delivery as per general law due to unseaworthiness; 2) There is no law or concept of law supporting the shipowners to accept the early redelivery of vessel if they have no legitimate interest in holding the charterer to continue their contract; 3) Failure of the charterer to redeliver the vessel after contract period (overlap) even though it is within reasonable time or in absence of expressed margin for redelivery, the charterer is in breach of contract and liable for damages after the contract period ended; 4) If hire is not paid on time, there are problems concerning withdrawing the vessel which differs from rescission of contract. It is also uncertain whether the shipowners can claim for interest and exercise lien upon sub-freight and sub-hire which shall be enforced under the provisions of an assignment of the right; and 5) Shipowners obligation of "due diligence" should be interpreted by analogy with Section 659 paragraph 3 of the Thai Civil and Commercial Code ("CCC"). Suggestions for the aboves are to interpret the contract in line with foreign laws. Section 368 of CCC may be a useful alternative. However, the enactment of specific law on Time Charter will clarify all the matters and prevent the court from applying Hire of Property Law as in the past. The specific law will also support maritime industry in Thailand.